It takes Two: Discovery of Spider Pax2 Duplicates Indicates Prominent Role in Chelicerate Central Nervous System, Eye, as Well as External Sense Organ Precursor Formation and Diversification After Neo- and Subfunctionalization - Janeschik, Matthias; Schacht, Magdalena Ines; Platten, Fabian; Turetzek, Natascha (Frontiers in Ecology and Evolution, 2022)
Paired box genes are conserved across animals and encode transcription factors playing key roles in development, especially neurogenesis. Pax6 is a chief example for functional conservation required for eye development in most bilaterian lineages except chelicerates. Pax6 is ancestrally linked and was shown to have interchangeable functions with Pax2. Drosophila melanogaster Pax2 plays an important role in the development of sensory hairs across the whole body. In addition, it is required for the differentiation of compound eyes, making it a prime candidate to study the genetic basis of arthropod sense organ development and diversification, as well as the role of Pax genes in eye development. Interestingly, in previous studies identification of chelicerate Pax2 was either neglected or failed. Here we report the expression of two Pax2 orthologs in the common house spider Parasteatoda tepidariorum, a model organism for chelicerate development. The two Pax2 orthologs most likely arose as a consequence of a whole genome duplication in the last common ancestor of spiders and scorpions. Pax2.1 is expressed in the peripheral nervous system, including both developing lateral eyes and external sensilla, as well as in the ventral neuroectoderm of P. tepidariorum embryos. This not only hints at a conserved dual role of Pax2/5/8 orthologs in arthropod sense organ development but suggests that in chelicerates, Pax2 could have acquired the role usually played by Pax6. For the other paralog, Pt-Pax2.2, expression was detected in the brain, but not in the lateral eyes and the expression pattern associated with sensory hairs differs in timing, pattern, and strength. To achieve a broader phylogenetic sampling, we also studied the expression of both Pax2 genes in the haplogyne cellar spider Pholcus phalangioides. We found that the expression difference between paralogs is even more extreme in this species, since Pp-Pax2.2 shows an interesting expression pattern in the ventral neuroectoderm while the expression in the prosomal appendages is strictly mesodermal. This divergence in expression patterns indicates both sub- and neofunctionalization after Pax2 duplication in spiders and thus presents an opportunity to study the evolution of functional divergence after gene duplication and its impact on sense organ diversification.